PENGARUH ALUR DISTRIBUSI IKAN BIJI NANGKA (Upeneus moluccensis Blkr.) TERHADAP CEMARAN MIKROBA DI PELABUHAN PERIKANAN NUSANTARA BRONDONG - Nirmala, Dwita; Latinsani, Annadiyah; Kusdarwati, Rahayu (Program Studi Akuakultur, Universitas Bangka Belitung, 2025)
The Nusantara Fishery Port of Brondong (PPN Brondong) has several dominant fish commodities, one of which is the Biji Nangka fish (Upeneus moluccensis Blkr.), a species commonly consumed for personal use as well as for industrial processing. The Biji Nangka fish caught by fishermen are stored in the fish hold (palkah) until the vessel lands at the port. Upon landing, the fishermen transfer the fish from the hold to the dock using baskets for sorting, after which the fish are stored in cool boxes for distribution to various destinations. The different storage conditions—fish hold, basket, and cool box—serve as potential media for bacterial growth due to poor sanitation and hygiene practices, as well as breaks in the cold chain during handling. Research findings indicate that the total bacterial count in fish stored in the hold is initially low but increases during storage in baskets and cool boxes. The lowest average organoleptic score was found in fish stored in baskets compared to those stored in the hold and cool box. Based on pH measurements, the Biji Nangka fish landed at PPN Brondong were categorized in the pre-rigor (6.9–7.2) and rigor mortis (6.2–6.6) phases. Furthermore, formalin testing on 54 fish samples showed that all the fish were negative for formalin content.